Case Report: Two Cases of Chemotherapy Refractory Metastatic Penile Squamous Cell Carcinoma With Extreme Durable Response to Pembrolizumab - Chahoud, Jad (Front Oncol, 2020)
BACKGROUND: Penile squamous cell carcinoma (PSCC) is a rare malignancy, and those patients with metastatic disease have limited treatment options. Treatment is largely comprised of platinum-based chemotherapy; however, patients progressing after initial chemotherapy have a median overall survival (OS) of less than 6 months. Based on a high percentage of PD-L1 expression in patients with PSCC, and its biological similarities to other squamous cell carcinomas, we present two patient cases treated with pembrolizumab with extraordinary durable treatment response far beyond treatment with standard therapy. MAIN BODY: The first patient is a 64 year old male with PSCC who was treated with neoadjuvant chemotherapy, partial penectomy, and adjuvant radiation prior to developing metastatic disease. He had a high TMB (14 mutations/Mb) and was started on pembrolizumab with a complete response, which has been maintained for 38 months. The second patient is an 85 year old male with PSCC who was treated with partial penectomy and adjuvant chemotherapy and radiation prior to developing metastatic disease. He had positive PD-L1 expression CPS 130) and was started on pembrolizumab with a partial response, which has been maintained for 18 months after starting treatment. CONCLUSIONS: These two cases of extreme durable response with pembrolizumab (with molecular data including TMB and PD-L1 status) represent a significant clinical benefit in this patient population. With limited treatment options that result in a median OS of less than 6 months, along with the toxicity profile of chemotherapy which may not be tolerated in elderly patients with comorbidities, this survival benefit with pembrolizumab, along with advances in tumor sequencing and clinical trials shows that there is a potentially significant benefit with novel therapies in this patient population.